1995
DOI: 10.1111/j.1447-0756.1995.tb01002.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bronchial Asthma on the Course of Pregnancy, Labour and Perinatal Outcome

Abstract: The course of pregnancy and labour, and perinatal outcome of 182 pregnancies complicated by bronchial asthma, over a 10-year period were studied. Antiasthmatic medications included oral and/or parenteral beta 2-agonists, theophylline, aminophylline, corticosteroids, and inhaled salbutamol and beclomethasone. A control group of 364 nonasthmatic gravidas was matched for age and parity. In asthmatic gravidas, antenatal complications mean duration of pregnancy (38.5 weeks), mode of delivery, incidence of prematuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 12 publications
4
95
1
2
Order By: Relevance
“…Administration of oxygen to mothers in labour resulted in increased umbilical cord O 2 values at delivery, suggesting that there is a relationship between maternal and foetal oxygen [76]. However, maternal hypoxia during asthmatic pregnancies has never been directly investigated in relation to foetal outcome and while it is unlikely to explain the finding of reduced female foetal growth in females with mild asthma [49], it may contribute to reduced growth in subjects who have been hospitalised with an exacerbation of asthma during pregnancy [26,56].…”
Section: Summary: Effect Of Asthma On Pregnancymentioning
confidence: 68%
See 3 more Smart Citations
“…Administration of oxygen to mothers in labour resulted in increased umbilical cord O 2 values at delivery, suggesting that there is a relationship between maternal and foetal oxygen [76]. However, maternal hypoxia during asthmatic pregnancies has never been directly investigated in relation to foetal outcome and while it is unlikely to explain the finding of reduced female foetal growth in females with mild asthma [49], it may contribute to reduced growth in subjects who have been hospitalised with an exacerbation of asthma during pregnancy [26,56].…”
Section: Summary: Effect Of Asthma On Pregnancymentioning
confidence: 68%
“…No significant increase in the rate of pre-term labour, low birth weight, caesarean section, perinatal mortality, haemorrhage or foetal distress was found in the asthmatic group compared with the control group. However, 15 of the asthmatics had a severe asthma attack during pregnancy, which required hospitalisation, and in these females there was a significant reduction in birth weight [26], suggesting that poorly controlled asthma may contribute to reduced foetal growth.…”
Section: Prospective Cohort Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the register study, no significant difference between social classes was observed in the caesarean section rate or in the cumulative incidence of asthma. Low birth weight has been associated with an increasing risk of asthma (40). Based on our data, this may be due to an association with the mode of delivery, as caesarean section carried a greater risk of asthma than birth weight per se; after adjusting with birth weight, only one-fifth reduction in the risk of asthma was seen.…”
Section: Discussionmentioning
confidence: 60%